Religious Moderation In Akidah Akhlak Teaching Materials At The Madrasah Aliyah - Usman, Usman; Subroto, Subroto; Al-Husna, Khofifah Indah; Aman, Aman; Siregar, Mulatua (Fahmina: Jurnal Pendidikan Islam, 2023)
Religious moderation is a topic of discussion that is widely discussed today considering the emergency cases of intolerance and radicalism in public life, especially in the world of education. Textbooks are certainly considered important as a form of character and personality formation that must support anti-radicalism and tolerance. Therefore, in writing this article, we will discuss the description of the moral creed textbook class X curriculum 2013 and describe the content of religious moderation values in the moral creed textbook class X curriculum 2013. This research is classified as library research with a qualitative approach. Data collection methods are used through documentation methods, and data is analyzed through Content analysis (content analysis). That is by linking religious moderation indicators to class X Akidah Akhlak textbooks at the Madrasah Aliyah level published by the Ministry of Religious Affairs. The result of this research is that there are several parts in each chapter of discussion, including: pearls of wisdom, perception, deepening of the material, student activities, attitude scales, summaries, final chapter assessments, case studies and exemplary stories. The content of religious moderation values contained in the Bina Akidah Akhlak KMA 2019 textbook for Madrasah Aliyah Class X is in accordance with the four basic values of religious moderation that must be instilled in the world of education, namely Tasamuh, 'Adalah, Tawazun and equality.